Underwater hyperspectral imaging system for deep-sea exploration - Xue, Qingsheng; Li, Hui; Lu, Fengqin; Bai, Haoxuan (Frontiers in Physics, 2022)
In this invited paper. As a technology which combined spectral technology and imaging technology, hyperspectral imaging technology can obtain the spectral and spatial information of the targets effectively. Hence the underwater hyperspectral imaging technology has a fast development since it was first used underwater. Many kinds of hyperspectral imagers used for underwater detection at different depth were developed. However, the underwater hyperspectral imager used at deep-sea were rarely reported while the required detection depth increased. To satisfy the deep-sea exploration requirements, an underwater hyperspectral imaging system was designed. An optical system with low F Number and compact structure was first designed. The F number of the system is 2.5. The focal length of the objective lens is 25mm, and the field of view of the objective lens is 35.2°.The wavelength range of the system is from 400nm to 1000nm, and the spectral resolution of the spectrometer is better than 3nm. The instrument cabin and other structures for waterproofing were designed. A minicomputer used for control communication, data acquisition and processing were equipped in the actual system. The isolation performance and imaging quality were test in laboratory environment. According to the test result, the system has a good imaging quality and spectral detection capability. And the system can be used at 6000m underwater, which may provide a new feasible technical scheme to the deep-sea exploration.